SANCTIONS POLICY IN THE INDONESIAN ACT. NO. 35 OF 2009 ON NARCOTICS - Indah Setyowati (Jurnal Pembaharuan Hukum, 2018)
Law is a legitimate product that is issued by the government / state is defined as a rule that should be known by the people or the public anywhere in the territory. The Act of the Republic of Indonesia Number 35 of 2009 on Narcotics is the latest drug laws supersede previous laws. Sanctions policy in this legislation is seen using a double track system which means that the policy of sanctions to use two-lane system is a criminal path for all the prohibited acts and course of action for users / abusers. While the sanctions policy are the following types may be criminal sanctions in principal and additional criminal, criminal sanctions are generally threatened by cumulation ie for example imprisonment with penalty, No weighting towards certain crimes when committed in an organized with conspiracy and carried out by the corporation and recidive. Experiment with a criminal offense the penalty is equal to committing a crime.